2016
DOI: 10.1038/ncomms11632
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for charge stripes in a layered cobalt oxide

Abstract: Recent experiments indicate that static stripe-like charge order is generic to the hole-doped copper oxide superconductors and competes with superconductivity. Here we show that a similar type of charge order is present in La5/3Sr1/3CoO4, an insulating analogue of the copper oxide superconductors containing cobalt in place of copper. The stripe phase we have detected is accompanied by short-range, quasi-one-dimensional, antiferromagnetic order, and provides a natural explanation for the distinctive hourglass s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 29 publications
(82 reference statements)
3
24
1
Order By: Relevance
“…Finally, there exist very recent studies of the charge correlations in cobaltates around 1/3 hole-doping, which can be interpreted in terms of an even more complex nano phase separation scenario, where in addition to the CBCO phases, some fractions of CSO phases also appear [24]. Note that nanoscale phase-separation phenomena are also recently discussed in the high-temperature superconducting cuprates [25], iron chalcogenides [26,27], and other superconductors [28].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Finally, there exist very recent studies of the charge correlations in cobaltates around 1/3 hole-doping, which can be interpreted in terms of an even more complex nano phase separation scenario, where in addition to the CBCO phases, some fractions of CSO phases also appear [24]. Note that nanoscale phase-separation phenomena are also recently discussed in the high-temperature superconducting cuprates [25], iron chalcogenides [26,27], and other superconductors [28].…”
Section: Introductionmentioning
confidence: 88%
“…[18][19][20]30], it was shown that there are no apparent indications for CSO correlations in La 2−x Sr x CoO 4 around 1/3 or 0.4 hole-doping for smaller or zero values of L. To clarify the origin of the recently observed signals at the tail of the checkerboard charge-ordering peaks for large values of L in Ref. [24], we have also investigated the charge correlations in La 2−x Sr x CoO 4 around 1/3 doping systematically.…”
Section: A Charge Correlationsmentioning
confidence: 98%
“…In the case of La 2−x Sr x CoO 4+δ an alternative scenario for the hourglass excitation spectrum arising from disordered checkerboard charge-ordered state has been proposed [8]. With the recent direct evidence of charge stripe order in La 2−x Sr x CoO 4+δ , the origin of the magnetic hourglass excitation spectrum is in dispute in this material [9].In LSNO magnetic excitations of the charge stripe electrons are observed [10], whereas half-filled charge stripes in the cuprates appear to have no interunit cell spin interactions, and * pgfreeman@uclan.ac.uk the spin state of the charge stripes in LSCoO is effectively S = 0 [1,2]. In the case of the cuprates there is evidence for a Q = 0 intraunit cell magnetic order from certain experimental techniques [11], this is apparently affected by charge stripe order in La-based cuprates possibly indicating the involvement of spins of half-filled stripes [12].…”
mentioning
confidence: 95%
“…In the case of La 2−x Sr x CoO 4+δ an alternative scenario for the hourglass excitation spectrum arising from disordered checkerboard charge-ordered state has been proposed [8]. With the recent direct evidence of charge stripe order in La 2−x Sr x CoO 4+δ , the origin of the magnetic hourglass excitation spectrum is in dispute in this material [9].…”
mentioning
confidence: 97%
“…Instead, checkerboard charge correlations were detected, and the hourglass spectrum could be explained in by a novel nano phase separation scenario based on La 2 CoO 4 -like undoped clusters and La 1.5 Sr 0.5 CoO 4 -like checkerboard charge ordered clusters [2][3][4][5][6]. Nevertheless, the discussion of the possible presence or absence of additional fractions of charge stripes in these cobaltates still continues [7].…”
Section: Introductionmentioning
confidence: 99%